The Impact of Incarceration on Women's Mental Health: Responses From Women in a Maximum-Security Prison. (January 2013) - Harner, Holly M.; Riley, Suzanne
Many women enter prison with significant mental health conditions. Without appropriate intervention during incarceration, there is the potential for these conditions to worsen during confinement. As a result, women, most of whom will eventually be released from prison, might return to their families and communities with even more complex mental health needs. We examined women's perceptions of how incarceration had affected their mental health. Our study approach included descriptive surveys and focus groups with women in prison. Our analysis revealed that women's mental health might worsen, might improve, or might remain the same as a result of incarceration. Women's accounts also provide evidence to support the need for all women's correctional institutions to adopt a trauma-informed approach to care of this vulnerable population.